Ideological discussions and the search for the historical subjectivity of Kazakh society in the twentieth century - Abylkhozhin, Zhulduzbek B.; Krupko, Igor V. (The New Research of Tuva, 2024)
The article examines the impact of the ideas of cultural hierarchy (imaginary low — high levels) and post-nomadic traumas (transformed culture of former nomadic society) on the discourse of Kazakh intellectuals, who in the twentieth century began searching for the historical identity of the Kazakh people. The authors note that sedentarism (the view of the settled world towards the nomadic world) is rooted in ideological priorities and the dialectic of narratives about the search for the historical identity of Kazakh society. The destruction of the traditional way of life for Kazakhs as a result of forced collectivization and sedentarization in the 1920s and 1930s continued to be discussed in scientific and political discourse. Many members of the Kazakh intellectual community in the 1950s and 1970s produced historical and cultural narratives about the idea that nomadic culture was backward. However, there were also attempts to overcome the cultural trauma of being seen as “unhistorical”. The accepted way to overcome this trauma within the existing hierarchy was through the scientific and ideological exploration of the archaeological heritage of settled agricultural cultures on the territory of Kazakh SSR. At the same time, some representatives of the new generation of Kazakh intelligentsia (O. O. Suleimenov, M. M. Auezov, N. E. Masanov) implemented the scientific and cultural incorporation of the historical subjectivity of the post-Nomads into the world history of civilization, without distancing themselves from the nomadic cultural heritage. However, almost a century later, the influence of the sedentarian hierarchies continues to persist in scientific, public and even official historical narratives of the 21st century.